Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1945
DOI: 10.1086/144699
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report on Chromospheric Spicules of Extremely Short Lifetime.

Abstract: Small spikes of chromospheric material, observed in Ha with the coronagraph and quartz-polaroid monochromator, are described. These spicules, seen in polar regions of the sun, have very brief lifetimes, amounting on the average to 4 or 5 minutes. The typical spicule is low in brightness and has a height at maximum of less than 15 seconds of arc. At least in polar regions, they appear to be present in greater or smaller numbers at all times. The spicules are apparently distributed at random in the polar regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

1952
1952
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 0 publications
0
44
0
2
Order By: Relevance
“…Already Labonte (1979) pointed out that the total magnetic flux of the QS exceeds the flux contained in ARs by far and that it drives activity, such as spicules. These were first observed in Hα and described as "small spices of chromospheric material" (Roberts 1945). Ephemeral ARs (see Sect.…”
Section: Quiet-sun Magnetic Fieldsmentioning
confidence: 99%
“…Already Labonte (1979) pointed out that the total magnetic flux of the QS exceeds the flux contained in ARs by far and that it drives activity, such as spicules. These were first observed in Hα and described as "small spices of chromospheric material" (Roberts 1945). Ephemeral ARs (see Sect.…”
Section: Quiet-sun Magnetic Fieldsmentioning
confidence: 99%
“…They were first observed by Secchi (1877) and called "spicules" by Roberts (1945). Spicules are best viewed at the solar limb as bright features against the dark background of the solar corona in Hα and Ca ii images.…”
Section: Introductionmentioning
confidence: 99%
“…The upper edge of the chromosphere seen at moderate resolution in strong chromospheric emission lines is rather "blurred" as it consists of the mixture of a large number of jet-like dynamic spicules and of coronal plasma between them. Many past observations showed that at the epoch of solar minimum the extension of the chomosphere near the poles is systematically higher than at the equator ( [3,24,25]) and modern precise measurements confirmed and substantiated these early suggestions ( [1,26]). The amount of prolateness depends of phase of the solar cycle, of the behavior of spicules and possibly of the inter-spicule matter.…”
Section: Discussionmentioning
confidence: 92%